2017
DOI: 10.1136/thoraxjnl-2016-209023
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, observational cohort study of the seasonal dynamics of airway pathogens in the aetiology of exacerbations in COPD

Abstract: BackgroundThe aetiology of acute exacerbations of COPD (AECOPD) is incompletely understood. Understanding the relationship between chronic bacterial airway infection and viral exposure may explain the incidence and seasonality of these events.MethodsIn this prospective, observational cohort study (NCT01360398), patients with COPD aged 40–85 years underwent sputum sampling monthly and at exacerbation for detection of bacteria and viruses. Results are presented for subjects in the full cohort, followed for 1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
197
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(215 citation statements)
references
References 36 publications
12
197
3
3
Order By: Relevance
“…There are reports indicating that HRV can infect monocytes/macrophages in vitro and in vivo [7,14,15,20,21,23]. We first found that post-HRV16 exposure, macrophages did not internalise a range of gram-positive and gramnegative bacteria that are frequently associated with exacerbations [20]. We first found that post-HRV16 exposure, macrophages did not internalise a range of gram-positive and gramnegative bacteria that are frequently associated with exacerbations [20].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…There are reports indicating that HRV can infect monocytes/macrophages in vitro and in vivo [7,14,15,20,21,23]. We first found that post-HRV16 exposure, macrophages did not internalise a range of gram-positive and gramnegative bacteria that are frequently associated with exacerbations [20]. We first found that post-HRV16 exposure, macrophages did not internalise a range of gram-positive and gramnegative bacteria that are frequently associated with exacerbations [20].…”
Section: Discussionmentioning
confidence: 71%
“…A recent study demonstrated that epithelial cells directly enhance the replication of rhinovirus in monocytes [15]. However, mounting evidence shows that HRV can infect the lower respiratory tract in patients with chronic inflammatory diseases including chronic obstructive pulmonary disease (COPD) driving disease exacerbations [17][18][19][20]. However, mounting evidence shows that HRV can infect the lower respiratory tract in patients with chronic inflammatory diseases including chronic obstructive pulmonary disease (COPD) driving disease exacerbations [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Severe infections are often associated with chronic lung diseases, like severe asthma and chronic obstructive pulmonary disease (COPD), both of which are not only associated with neutrophilia and increased LL-3716 17 but also a dysbiosis of the lung microbiome,18 with increased abundance of Proteobacteria spp and non-typeable Haemophilus influenzae (NTHi) in particular. IL-1β is already increased in the lungs of patients with COPD who are colonised with NTHi,19 and compellingly in a longitudinal cohort of patients with COPD, we observed that NTHi colonisation increased the risk of a viral infection being associated with an exacerbation compared with the presence of virus alone 20. NTHi is also frequently detected in the sputum of hospitalised patients with pneumonia 21.…”
mentioning
confidence: 51%
“…Another study investigating etiologic agents causing AECOPD found Haemophilus influenzae, Moraxella catarrhalis, and rhinovirus as the most incident pathogens. Therefore, the vaccination spectrum for COPD should be more diverse to enclose other potential pathogens causing AECOPD [14], and new vaccines against these pathogens should be developed.…”
Section: Discussionmentioning
confidence: 99%